Experimental measurements and modelling of carbon dioxide solubility in aqueous AMP/MDEA and Piperazine/MDEA blends - Suleman, H. (Elsevier B.V., 2018)
Experimental measurements and modelling of carbon dioxide solubility were performed in separate aqueous blends of 2-amino-2-methyl-1-propanol (AMP)/N-methyldiethanolamine (MDEA) and piperazine (PZ)/MDEA in the high gas loading region. The experimental loadings of carbon dioxide were measured at various parametric values of pressure (102.5â4110 kPa), temperature (303.15â343.15 K) and solvent concentration (1 + 1 and 2 + 2 M). It is shown that addition of AMP and PZ to MDEA improved the overall carbon dioxide loadings and were in excellent agreement with the experimental values found in open literature. The experimental results were accurately correlated by a hybrid KentâEisenberg model, with an average deviation of 10.5. Furthermore, the model satisfactorily estimated the carbon dioxide solubilities in AMP/MDEA and PZ/MDEA blends at other parametric conditions. Â© 2018 Elsevier B.V.